The language of flowers : a novel - Diffenbaugh, Vanessa (New York : Ballantine Books, 2011)
"The story of a woman whose gift for flowers helps her change the lives of others even as she struggles to overcome her own past"--Provided by publisher.
Keywords: Young women -- Fiction; Florists -- Fiction; Flower language -- Fiction; San Francisco (Calif.) -- Fiction; Love stories